Identifikasi Simptom Penyebab Perundungan: Upaya Menciptakan Sekolah Ramah Anak - Handoyo Prasetyo; Bambang Waluyo; Subakdi Subakdi; Beniharmoni Harefa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The topic of bullying is never discussed from time to time, the phenomenon of bullying is like an epidemic or a rapidly spreading disease that causes many victims. The phenomenon of bullying is increasingly growing because currently it is a modern era that cannot be separated from technological developments which have positive and negative impacts. Television or social media shows are easier for school-age children to imitate, especially behavior that is considered not good. For example, a fight scene that ends in bullying. Bullying occurs at every school level, from elementary school, middle school, high school to university, both public schools and religious schools and Islamic boarding schools. Bullying is carried out by students, teachers, parents and also school principals with the majority of victims being students. In order to protect and prevent bullying, the government has issued many laws such as the Child Protection Law, the Children's Criminal Justice System Law, the Minister of Education, Culture, Research and Technology Regulations, the Minister of State for Women's Empowerment and Child Protection Regulations, Guidebooks and Programs Anti-bullying from each school and various forms of efforts to anticipate and prevent bullying in schools. In fact, the various regulations issued by the Government have not been able to overcome bullying behavior, which will even increase by 30% in 2023 compared to 2022. This research will complement other research that has been carried out previously, using a different perspective, namely with the concept of sustainability. activities through the PDCA (Plan, Do, Check, Action) system, which requires stakeholders (Government, Teachers, Parents, Students, Law Enforcement and all parties involved) to carry out systematic and holistic prevention efforts, which in every The steps taken must always be reviewed to find out whether the work plan made has succeeded in preventing or not being effective.